Perspectives of Business Personnel on Force Majeure as A Reason For Cutting Work Relationship in The Pandemic Time Covid -19 (Faculty of Law, Universitas Negeri Semarang, 2020)
The COVID-19 Pandemic outbreak that was experienced in almost all countries in the world, including Indonesia, added challenges as well as new anxiety for businesses and workers. The spread of COVID-19 in Indonesia increasingly adds to the difficulty of the national industrial sector. The COVID-19 pandemic can be categorized as a Force Majeure. It is a condition outside the wishes of the parties and cannot be predicted in advance, so the obligations specified in the contract cannot be fulfilled. Force Majeure can be used as a reason for companies to terminate their employees (PHK), as stipulated in